A journey through transportation : from hot lava to a spy rocket... - Jackson, Tom, 1972- (Jackson, Tom, 1972- Follow the link., 2017)
How did a volcanic eruption lead us to a robot spaceplane? Follow the link to find out... Want to know how a simple clock helped sailors find their way? Or how sand was used to make the toughest spacecraft ever? A Journey Through Transportation reveals the amazing and often surprising links that have shaped science. Discover the inspiration behind great inventions and find out what lies ahead for the future of transportation.